(Nu^N)QÆWSXKE SAMOWRQDUWANNQ(B: (NPRAKTIKA WPROWADVENNQ (B:s)E (NNAW^ALXNO(B-(NMETODI^NIJ POS)QÆBNIKs)E ((NkI)QÇW (B:s)E (NpLEQDI(B,s, 2005)
(NzB)QÆRNIK MATERÆALÆW Z DOSWÆDU ORGANÆZACÆÇ U^NÆWSXKOGO SAMOWRQDUWANNQs)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NoRGAN)QÆZACÆQ NAW^ALXNIH ZAKLADÆWs)E -- (Nu^N)QÆWSXKE SAMOWRQDUWANNQs)E; (NSAMOWRQDUWANNQs; (NORGAN)QÆZACÆQs)E; (NC)QÆNNOSTÆs)E; "(N[KOLA SP)QÆWROBÆTNICTWA(B"s)E